An Error Analysis of 4th Semester College Students’ Translation By Using ATA Standardize Error Making Theory - Nurkholis, Akhmad; Fatmasari, Yuniar (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2023)
This research aims to find out the errors occur in students’ translation product, this is a qualitative research and the object of the research is 4th- semester college students. The data was analyzed by using an error category by ATA’s standardized error making. The analysis reveals that the most errors occured on students’ translation are literalness: 258 occurrences (30,71%), misunderstanding: 221 occurrences (26,31%), terminology: 111 occurrences (13,21%), the last omission: 88 occurrences (10,48%), faithfulness: 73 occurrences (8,69%), then the next is grammar: 40 occurrences (4,76%), cohesion: 38 occurrences (4,52%) and the last is syntax: 11 occurrences (1,31%). Based on the research result it can be concluded that students’ knowledge of translation techniques is very limited, that caused errors in translating the text. In translating process, they must master translation techniques to translate certain text. This research will probably give some literature about the errors made by students, so it can be used by the teacher of translation material to give more lesson of translation techniques and give them more exercise in translating certain text. Then for the students, this research can be used as guidance to be more aware of errors that occur in translation process, for another researcher should conduct other research with another point of view.